2017
DOI: 10.1590/s1518-8787.2017051006884
|View full text |Cite
|
Sign up to set email alerts
|

Trend of leprosy in individuals under the age of 15 in Mato Grosso (Brazil), 2001-2013

Abstract: OBJECTIVE To identify the historical trend of leprosy epidemiological indicators in individuals under the age of 15 in the state of Mato Grosso.METHODS Descriptive study with trend analysis of leprosy indicators in individuals under the age of fifteen registered in the Mato Grosso’s System for Notifiable Diseases between 2001 and 2013. We used the Prais-Winsten procedure for analyzing generalized linear regression at a significance level of 5%. We considered as increasing time series when the annual percent ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
1
11

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(49 citation statements)
references
References 17 publications
3
26
1
11
Order By: Relevance
“…Corroborating with our result, it had already been evidenced a decrease of this illness in children under 15 years in Maranhão (9) . In Brazil, there was also a decrease in Pará (9) , Mato Grosso (4,9) , and in the capital of Ceará (16) . Some countries have also showed a decrease in the trend of the disease in this age group (1,17) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Corroborating with our result, it had already been evidenced a decrease of this illness in children under 15 years in Maranhão (9) . In Brazil, there was also a decrease in Pará (9) , Mato Grosso (4,9) , and in the capital of Ceará (16) . Some countries have also showed a decrease in the trend of the disease in this age group (1,17) .…”
Section: Discussionmentioning
confidence: 99%
“…The fact that children under the age of 15 have been ill makes is concerning because it indicates that a significant number of cases have not been detected or treated in a timely manner to break the disease transmission chain (14) . In addition, it may be suggested undiagnosed home contact (4) . It is worth remembering that the transmission of the disease is not restricted to the household (14) , thus, this highlights the important role of extra-household or social contacts in the transmission chain of leprosy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of clinical profile, studies in different regions of Brazil have also shown high proportions of multibacillary cases and more severe clinical forms of leprosy, as well as degrees I and II of physical disability at the time of diagnosis [15][16] This shows that the transmission dynamics of leprosy have remained in the evaluated areas, and also signals the occurrence of late diagnosis.…”
Section: Socioeconomic and Clinical Characteristics Of Study Participmentioning
confidence: 93%
“…In a study conducted in the state of Mato Grosso, evaluating the period from 2001 to 2013, there was a 6.7% increase in the proportion of multibacillary cases and 14% in cases with grade 2 of physical disability at the time of diagnosis of the disease [21].…”
Section: User Profilementioning
confidence: 99%